FRI0187 Radiographic progression by disease activity states in patients with rheumatoid arthritis treated with sb2 or reference infliximab. (15th June 2017) - Smolen, JS; Choe, J-Y; Keystone, E; Rho, YH; Lee, Y; Lee, S
Abstract : Background: Based on the totality of evidence, SB2 has shown to be similar with reference infliximab (INF) and has been approved as a biosimilar by the European Medical Agency. It is, however, hitherto unknown, if SB2 also shares similar structural efficacy in the different disease activity states when compared with INF. Objectives: To evaluate the disease activity by simplified disease activity index (SDAI) and clinical disease activity index (CDAI) at weeks 14, 30 and 54 in patients with rheumatoid arthritis (RA) treated with SB2 or INF from a phase III study and to assess the radiographic progression at week 54 in patients by disease activity states (remission, low disease activity [LDA], moderate disease activity [MDA], or high disease activity [HDA]). Methods: Patients with RA were randomised to receive either SB2 or INF 3 mg/kg at weeks 0, 2, 6, and then every 8 weeks thereafter until week 46 with background methotrexate. Dose increments were allowed after week 30 by 1.5 mg/kg up to a maximum dose of 7.5 mg/kg. Disease activities by SDAI, and CDAI were compared at weeks 14, 30, and 54. The radiographic progression was measured by modified Total Sharp Score (mTSS) at weeks 0 and 54. Results: Up to week 54, comparable proportions of patients achieved ACR-EULAR-index remission between SB2 and INF (by SDAI: 13/279 [4.7%] vs. 13/283 [4.6%] at week 14; 24/250 [9.6%] vs. 29/263 [11.0%] at week 30; 34/226 [15.0%] vs. 24/224 [10.7%] at week 54; by CDAI: 12/279 [4.3%] vs. 12/283 [4.2%] at week 14; 22/253 [8.7%] vs. 31/265 [11.7%] at week 30; 33/227 [14.5%] vs. 24/225 [10.7%] at week 54 in SB2 and INF, respectively). The proportions of radiographic non-progressors (defined as change in mTSS ≤0) by disease activity were comparable between SB2 and INF at week 14, 30 and 54 (Table 1 ). Patients treated with SB2 as well as INF also exhibited the lowest progression of radiographic damage in remission and the largest progression in HDA, but also very small increases in mTSS in LDA and MDA, in line with previous findings on INF. Conclusions: The proportion of patients achieving remission or LDA was comparable up to week 54 upon treatment with both SB2 and INF. Inhibition of radiographic progression was also comparable in each disease activity state. The proportion of radiographic non-progressors was also similarly high in patients achieving remission, and overall very low radiographic progression rates were seen even in LDA and MDA in both treatment arms. These data further confirm the comparability of SB2 and INF. Disclosure of Interest: J. S. Smolen Consultant for: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene, Glazo, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung Bioepis, Sanofi, UCB, J.-Y. Choe Consultant for: Samsung Bioepis, E. Keystone Consultant for: Pfizer, Roche, Janssen, Amgen - consultant/Pfizer, Roche, Janssen, Amgen, BMS, Merck. Merck, Celltrion, Samsung Bioepis, Y. H. Rho Employee of: Samsung Bioepis, Y. Lee Employee of: Samsung Bioepis, S. Lee Employee of: Samsung Bioepis